How “Good” Governance in Indonesia? A Systematic Literature Review - Polrendyo Polrendyo; Ika Devy Pramudiana; Eny Haryati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This article presents a systematic literature review on the application of good governance principles in Indonesia from 2019 to 2025. It explores the development of good governance concepts, including key principles such as transparency, accountability, participation, law enforcement, and public service effectiveness. The study also addresses the significant challenges faced in implementing these principles, such as pervasive corruption, a complex bureaucratic culture, and disparities in human resource capacity across regions. The methodology applied in this research is a systematic literature review, complemented by bibliometric analysis using VOSviewer, which maps the relationships between key concepts and trends identified in the related research. The findings reveal that the principles of good governance have been integrated across various sectors, such as local government, education, healthcare, environmental management, and digital services, showing the broad scope of its application. However, despite these efforts, challenges such as widespread corruption, bureaucratic resistance, digital infrastructure gaps, and low public participation—especially in remote and rural areas—remain significant barriers. This study emphasizes the need for a comprehensive and integrated approach to overcoming these obstacles, suggesting that institutional strengthening, technological innovation, inclusive public participation, and sustained political commitment are essential to realizing good governance. Furthermore, the research contributes to the development of more effective and sustainable governance policies, offering insights for enhancing governance practices and strategies in Indonesia moving forward. The study advocates for long-term solutions to improve governance effectiveness and ensure equitable and inclusive public services.